GREEN SYNTHESIS OF NANO-SILVER PARTICLES FROM LEAF AND STEM EXTRACTS OF IBOZA (TETRADENIA RIPARIA) - Shaik, Shakira; Mkize, Lwamkelekile; Khumalo, Mthokozisi; Singh, Nisha (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Secondary metabolites derived from plant extracts can be used in the reduction of metal salts into their respective nanoparticles using simple, environmentally friendly and cost effective green synthesis techniques. Metal nanoparticles have important applications in medicine and agriculture. The leaves of Tetradenia riparia (Iboza), an important medicinal species in South Africa, are reported to contain various terpenoids and pyrones which can be used in the reduction of silver nitrate (AgNO3) to nano-silver particles. Materials and Methods: Fresh leaves and stems of Iboza were oven-dried, crushed, extracted in water and methanol and filtered followed by incubation with AgNO3. Synthesized nano-silver particles were characterised using ultraviolet visible (UV-Vis) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy and Fourier transform infrared (FTIR) spectroscopy. Results: The bio-reduction of metal ion to base metal was rapidly conducted in a single step and at room temperature and pressure. UV-Vis spectra showed the characteristic surface plasmon resonance band of the synthesized nano-silver particles at 410 nm for all extracts. SEM analysis revealed predominantly aggregated spherically-shaped nano-silver particles with a size range of 20-50 nm and an average diameter of 26 nm. The presence of elemental silver in the nanoparticles was confirmed by EDX at 3 keV. As revealed by FTIR analysis, the reducing agents included terpenoids and pyrones which were responsible for reducing and capping the nano-silver particles. Conclusion: Both methanol and aqueous-derived extracts of Iboza leaves and stems can be used to synthesize nano-silver particles. FTIR evidence suggests that the reduction of the silver ions and the synthesis of the nanoparticles may have been actioned by various terpenoid and pyrone compounds found in the plant parts.